Antibiotic sensitivity pattern of Salmonella serotypes in patients with enteric fever in a teaching hospital - Muhammad, Riaz; Ali, Zafar; Mehmood, Khalid; ., Ziauddin; Afridi, Abdur Rahman; Bari, Fazal (Journal of Postgraduate Medical Institute, 2013)
Objective: To determine the sensitivity of salmonella serotypes to antibiotics in patients with enteric fever. Methodology: This descriptive study was carried out in medical units of Lady Reading Hospital Peshawarfrom January 2008 to December 2011. Patients were included by consecutive sampling technique. Bloodsamples were collected from patients with clinically suspected enteric fever and were sent to hospitallaboratory for culture and sensitivity(C/S). Salmonella colonies were identified using standard biochemicaltests including fermentation of glucose, negative urease reaction, lysine decarboxylase, negative indoletest, H2S production, and fermentation of dulcitol. Serological confirmation tests included polyvalent antiserafor flagellar and somatic antigens. Antibiotic susceptibility was checked by Kirby- Bauer disc diffusionmethod for 22 antibiotics. Results: Blood cultures of 106(61%) patients out of 173 patients were positive for salmonella species.Salmonella Typhi was found in 54.7% while salmonella paratyphi A in 32.1% and B in 13.2%. The sensitivityof salmonella species for ceftriaxone and ceftazidime was found to be 100%, followed by imipenem(98.1%) and meropenem (96.2%). The sensitivity of drugs like amoxicillin, chloramphenicol and co-trimaxazolewere 2.8%, 12.3% and 22.6% respectively. Regarding quinolones, most sensitive was moxifloxacin49.1%, followed by ciprofloxacin 48.1%. Salmonella typhi was fully sensitive to meropenum, ceftriaxoneand cetazidime while paratyphi A or B was fully sensitive to ceftriaxone, ceftazidime and imipenem. Conclusion: The sensitivity of salmonella species was very low to the first line agents such as amoxicillin,chloramphenicol and co-trimaxazole. Salmonella species were fully sensitive to third generation cephalosporinssuch as ceftriaxone and ceftazidime.